Státní inspekce - druhy, postavení, působnost, pravomoc - Chládová, Šárka (Univerzita Pardubice, 2006)
Bakalářská práce se zabývá problematikou správního dozoru, který vykonávají specializované dozorčí orgány - státní inspekce. První část pojednává obecně o správním dozoru. Druhá část je zaměřena na působnost a pravomoc státních inspekcí působících v ČR. Třetí část je pak věnována kontrolní činnosti České obchodní inspekce.

This bachelor work is devoted to the questions of administrative supervision that are carried out by specialized supervisory authority - state inspection. The first part generally deals with the administrative supervision, the second part is focused on field of activity and competence of state inspection operating in the Czech Republic and the third part on the controlling of Czech Commercial Inspection.
State inspection - types, position, field of activity, competence
Keywords: administrative supervision; supervisory authority; state inspection; Control; field of activity; competence; správní dozor; dozorčí orgán; státní inspekce; Kontrola; působnost; pravomoc